STUDI SOSIOLINGUISTIK ALIH KODE DAN CAMPUR KODE BAHASA PAKSEL (NGAPAK JAKSEL) DALAMVIDEO TIKTOKRAFLY - Rahayu, Feri Kanti; Festiyanti, Wilda Putri (An-Nas, 2024)
“Language is a form of communication to convey information, thoughts, feelings, and goals or intentions to other people. In the era of globalization, the use of more than one language is often experienced by someone who is called a "bilingual" or "multilingual" person. The ability to use more than one language in communication is often encountered in everyday life. One example is Rafly Paksel's TikTok video, where Rafly Paksel always uses more than one language when communicating or speaking, namely combining or inserting Indonesian with Javanese. So from this phenomenon the researcher aims to identify the types of code switching and language code mixing that Rafly Paksel uses in his TikTok videos. This research is a qualitative descriptive research with data collection methods based on primary data sources and secondary data. "Based on data analysis, the phenomenon of code switching and code mixing that Raply Paksel uses when speaking in his TikTok videos is inter sentential type code switching, and the code mixing that is often used by Raply Paksel is intra sentential mixing."